Online tool characteristics in value co-creation - Möttönen, Juha (2023)
During the year 2020, the way to work changed dramatically as the COVID-19 pandemic shook the world. Because drastic measures were needed to prevent the virus from spreading, more personnel were recommended to work from home offices. On the other hand, this remote work development meant more personnel working with ICT-enabled collaborative tools across the single case study organisation. This thesis approaches the research problem introduced with a systematic literature review, a theme-based interview data collection and a thematic analysis. Within the systematic literature review, the aim is to find out what is already known about the research problem through systematic methods of finding and analysing data. Empirical studies, in turn, are reflected in systematic literature review findings, and the data is collected through theme-based interviews. Finally, from these two approaches, the details of the findings are done and shown. According to the results, characteristics can be found that promote value co-creation. These characteristics allow a dyad exchange of services. Implications, however, are based on a single case context. Within the study context, it was identified that the tools should have characteristics that promote real-time information sharing, structure, and methods to promote trust between the stakeholders within value co-creation.